The Interleukin-23/Interleukin-17 Axis Links Adaptive and Innate Immunity in Psoriasis - Schön, Michael P.; Erpenbeck, Luise (Frontiers in Immunology, 2018)
Research into the pathophysiology of psoriasis has shed light onto many fascinating immunological interactions and underlying genetic constellations. Most prominent among these is the crosstalk between components of the innate and the adaptive immune system and the crucial role of interleukins (IL)-23 and -17 within this network. While it is clear that IL-23 drives and maintains the differentiation of Th17 lymphocytes, many aspects of the regulation of IL-23 and IL-17 are not quite as straightforward and have been unraveled only recently. For example, we know now that Th17 cells are not the only source of IL-17 but that cells of the innate immune system also produce considerable amounts of this central effector cytokine. In addition, there is IL-23-independent production of IL-17. Besides other innate immune cells, neutrophilic granulocytes prominently contribute to IL-17-related immune regulations in psoriasis, and it appears that they employ several mechanisms including the formation of neutrophil extracellular traps (NETs). Here, we strive to put the central role of the IL-23/IL-17 axis into perspective within the crosstalk between components of the innate and the adaptive immune system. Our aim is to better understand the complex immune regulation in psoriasis, a disorder that has become a model disease for chronic inflammation.